Structure elucidation of and synthetic approaches to monatin, a metabolite from Schlerochiton ilicifolius - Ackerman, Louis Gabriel Jozua (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University , 1990.